Playing Exergames Facilitates Central Drive to the Ankle Dorsiflexors During Gait in Older Adults; a Quasi-Experimental Investigation - de Bruin, Eling D.; Patt, Nadine; Ringli, Lisa; Gennaro, Federico (Frontiers in Aging Neuroscience, 2019)
Gait training might be of particular importance to reduce fall risk in older adults. In the present study we explore the hypothesis that video game-based training will increase tibialis anterior muscle EMG-EMG coherence and relates to functional measures of lower limb control. We focus on video game-based training, which necessitates the subject’s ability to lift the toes and to place the feet on different target zones as a requirement to successfully play the game. We hypothesize that this type of training will lead to progressive changes in the central motor drive to tibialis anterior motor neurons and to an improvement in the control of ankle dorsiflexion during gait. Results showed a significant difference against 0 in the experimental POST condition in dual-task walking and beta Frequency Of Interest (p = 0.002). Walking under dual task condition showed significant change over time in minimal Toe Clearance for both the left (χ2(2) = 7.46, p =0.024, n = 20) and right (χ2(2) = 8.87, p = 0.012, n = 20) leg. No change in lower extremity function was detectable. Overall we conclude that the initiation of an exergame-based training in upright standing position improves neural drive to the lower extremities in older adults and seems an acceptable form of physical exercise for this group.